The Effect Of Workload And Work Environment On Organizational Commitment (Study On Non-Permanent Employees Of Bni Branch Office Palembang) - Ihzamahendra ihzamahendra; Marlina Widiyanti; Muhammad Yusuf; Muhammad Ichsan Hadjri (Journal of Social Research, 2024)
This study was conducted with the aim of determining the influence of workload and work environment on organizational commitment to non-permanent employees of BNI Palembang branch office. The population used in this study is all non-permanent employees at PT Bank Negara Indonesia (Persero), Tbk Palembang Branch Office in 2024 as many as 108 employees. The number of respondents in this study is all non-permanent employees at PT Bank Negara Indonesia (Persero), Tbk Palembang Branch Office in 2024 as many as 108 employees spread across 16 Sub-Branch Offices and 1 Main Branch Office and all of them are the number of respondents in this study. The results of multiple linear regression analysis show that workload and work environment have a positive and significant effect on organizational commitment. Workload, is expected to provide time with appropriate working hours for employees. The work environment, it is expected that the company's management, especially the superiors at each branch office, will be more sensitive to the relationships established between fellow employees.